(untitled) (Iraqi Journal of Medical Sciences, 2018)
Background: Peripheral arterial disease (PAD) is one of the most common cardiovascular diseases in developed countries and is an emerging problem in developing countries. Duplex ultrasonography (DUS) has been used as the initial imaging modality in mild symptomatic PAD. Multi-slice helical CT angiography of arteries of the thigh represents a reliable means for the detection of relevant stenoses in patients with peripheral occlusive artery disease. Objective: To assess value of multi-detector computed tomography angiography (MDCTA) and to compare it with DUS to diagnose chronic ischemia of lower limbs. Methods: A prospective comparative study was conducted on 30 patients with chronic lower limbs ischemia of both limbs during the period from September 2015 to September 2016 at the Department of Diagnostic Radiology of Al-Imamein Al-Kadhimein Medical City, Baghdad, Iraq. DUS was done for all the patients and then MDCTA was done. Results: Thirty patients (20 males and 10 females) with a mean age of 57.1 ± 8.5 (range: 33 –80) years were included in this study. MDCTA detects 69 lesions (41 occluded segments and 28 stenotic segments) and DUS detects 58 lesions (35 occluded segments and 43 stenotic segments). In MDCTA, 8 patients (26.7%) had lesion in only one arterial segment, 13 patients (43.3%) had two segment lesions, 3 patients (10%) had three segment lesions, 4 patients (13.3%) with four lesions and only two patients (6.7%) had lesions in five arterial segments. Regarding the findings of the DUS one segment lesion was detected in 13 patients (43.3%), two segment lesions in 11 (36.7%), three segment lesions in 2 (6.7%), four segment lesions in 3 (10.0%) and only five segment lesions in only one patient (3.3). Furthermore, the measure of agreement between both MDCTA and DUS in the number of lesions detected revealed a good agreement between both tests, (Kappa = 0.81) with a percent agreement of (86.6%). Conclusion: Multi-detector CT angiography is a fast, accurate, safe and a minimally-invasive imaging modality which may be used in cases of PAD for diagnosis, grading and for preoperative assessment of lower limb arterial disease. Keywords: Multi-detector CT Angiography, chronic ischemia of lower limbs, doppler ultrasound Citation: Kadhim MA, Eisa YA, Mohammed SJ. Value of multi-detector CT angiography in chronic ischemia of lower limbs in comparison with the doppler ultrasound. Iraqi JMS. 2018; 16(2): 144-151. doi: 10.22578/IJMS.16.2.5